Noise-like pulse generation with tungsten trioxide/polydimethylsiloxane-clad microfiber saturable absorber - Abdul Hadi, Muhamad Amir Waliuddin; Muhammad, Farah Diana; Mohd Yusoff, Norita; Alresheedi, Mohammed Thamer; Goh, Chee Seong; Mahdi, Mohd Adzir (Wiley, 2022)
We report the formation of noise-like pulse (NLP) with tungsten trioxide/polydimethylsiloxane-clad microfiber saturable absorber integrated in a ring-cavity erbium-doped fiber laser. The NLP operation was confirmed by the presence of a coherence spike on top of a broad pedestal in the autocorrelation trace, with the measured pulse width value of 410 fs and 3.56 ps respectively. By increasing the pump power from the mode-locking threshold of 280–3300 mW, the spectral bandwidth was stretched from 22.3 to 22.8 nm, while the output power increased from to 1.9 to 24.3 mW. The maximum pulse energy of 3.5 nJ was generated at a repetition rate of 7 MHz. The signal-to-noise ratio was measured to be 53.8 dB, which indicated a good stability of pulse laser.